Chemically Stabilized and Functionalized 2D‐MXene with Deep Eutectic Solvents as Versatile Dispersion Medium. (20th January 2021) - Kim, Jeonghui; Yoon, Yeoheung; Kim, Seong K.; Park, Seungyoung; Song, Wooseok; Myung, Sung; Jung, Ha‐Kyun; Lee, Sun Sook; Yoon, Dae Ho; An, Ki‐Seok
Abstract: 2D transition metal carbides and nitrides, namely MXenes, are normally synthesized in acidic solutions and are delaminated in basic solutions. This results in versatile materials with unique physical/chemical properties suitable for various practical applications. However, solution‐based chemical treatments can affect the chemical structures of MXenes, which accelerates the oxidation reactions and degrades their intrinsic properties. Here, long‐term stable Ti3 C2 T x dispersion in deep eutectic solvents (DESs) that resisted oxidation degradation for up to 28 weeks is demonstrated. As an anti‐oxidative dispersion medium, DESs helped prevent oxidation of Ti3 C2 T x layers due to hydrogen bond accepting and donating molecules passivated surface of the Ti3 C2 T x . In addition, DES molecules in bulk solution can also be hydrated in the presence of water, which stabilizes reactive oxygen by forming stable DES‐water cluster. Therefore, the use of DESs enhanced the delamination of the Ti3 C2 T x nanosheets, while preventing oxidation of the nanosheets in solution and even in their dried state. As a result, thick and thin films of Ti3 C2 T x fabricated using DESs exhibited stable sheet resistance in comparison with pristine‐Ti3 C2 T x . In addition, Ti3 C2 T x dispersed in DESs can be applied as electrodes for electrochemical capacitors, in which they showed higher chemical stability and better performance than pristine Ti3 C2 T x . Abstract : In this article, it is found that polarized deep eutectic solvent (DES) molecules can also act as an effective intercalant to delaminate MXene. Moreover, the hydrogen bond accepting and donating molecules in DESs, which have strong interactions with the oxygen functional groups and unsaturated Ti vacancies in the defect sites of Ti3 C2 T x not only have the superb ability to disperse Ti3 C2 T x sheets, but also prevent oxidation in both the solution and dried phase.